Exploration of Creative Problem-Solving Learning Based on Design Thinking with HOTS Questions to Improve Students' Numeracy - Ratri Gita Wulandari; F.X Didik Purwosetiyono; Nizaruddin Nizaruddin (JURNAL PENDIDIKAN MATEMATIKA, 2025)
The study aims to examine the effectiveness of Creative Problem Solving (CPS) learning based on Design Thinking using HOTS (Higher Order Thinking Skills) questions to improve junior high school students' numeracy skills. This research employed a quasi-experimental method with a multiple-group pretest-posttest design, involving an experimental and a control class. Data were collected through numeracy tests, classroom activity observations, and student response questionnaires. The results indicated that students in the experimental class experienced a significant improvement in numeracy, with an average N-Gain score of 0.72, categorized as high. This learning approach also facilitated active student participation, increased interest in mathematics, and promoted independence in problem-solving. Students' attitudes toward numeracy tasks shifted from frustration to more adaptive strategies. Mastery learning was achieved classically, with posttest scores exceeding the Minimum Mastery Criteria (KKM). In addition to cognitive gains, students expressed positive perceptions of the learning approach, especially due to its contextual, challenging, and exploratory nature. Thus, design Thinking-based learning integrated with HOTS-CPS questions has been proven effective in enhancing students' numeracy and is recommended as an innovative strategy in support of the Merdeka Curriculum. Keywords: Design Thinking, HOTS, Numeracy